Tathawwur al-Alam al-Islamiy fi Libya wa Khashaishuhu - Dyabat, Etaher Ali Saad; Syafaq, Hammis (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2022)
Abstract:  In this article, the researcher presents the development of the Islamic world in Libya and beginning by talking about the entry of Islam into Libya and focusing on the Maliki school, which is one of the most prominent elements of this development, and then presents the role of the Senussi movement. It turns out that the entry of Islam to Libya and its development was early since the Islamic conquest of it in the first century AH and the seventh AD in the time of Caliph Omar bin Al-Khattab, and Libya embraced in the period of the Islamic conquest has the remains of some companions, may God be pleased with them, who were martyred in order to spread Islam in this country, the most famous of which are Al-Munaidher Al-Afriqi in the city of Tripoli, Ruwaifa Al-Ansari in the city of Al-Bayda, Abu Sajeef bin Qais in the city of Misrata, Zuhair Al-Balawi, Abu Mansour Al-Farsi and Abdullah bin Righteousness and both three in the city of Derna, and the development of Islam with the spread of the Maliki school and the emergence of scholars who contributed to its dissemination not only in Libya but in all countries of the Arab Maghreb, such as Sheikh Ali bin Ziyad Trabelsi, where the Maliki school was among the foundations in the development of Islam in Libya, and was associated with various aspects and formed an identity for Libyans throughout the ages, and the Senussi method formed a significant role in the development of Islam in Libya and played an essential role in spreading Maliki jurisprudence and the pure Sufi way far away On heresies and superstitions and in the dissemination of Maliki jurisprudence, as well as in the jihad movement against the Italian colonizer. Keywords: evolution, world, sect, Islam, Libya. الملخص: في هذه المقالة يعرض الباحث لتطور العالم الإسلامي في ليبيا والبداية بالحديث عن دخول الإسلام لليبيا ومركزا على المذهب المالكي الذي يعد من أبرز عناصر هذا التطور ثم يعرض لدور الحركة السنوسية. يتبين أن دخول الإسلام لليبيا وتطوره بها كان مبكرا منذ الفتح الإسلامي لها في القرن الهجري الأول السابع الميلادي في زمن الخليفة عمر بن الخطاب ، واحتضنت ليبيا في فترة الفتح الإسلامي لها رفات بعض الصحابة رضي الله عنهم الذين استشهدوا في سبيل نشر الإسلام في هذا البلد من أشهرهم المنيذر الأفريقي في مدينة طرابلس، ورويفع الأنصاري في مدينة البيضاء، وأبو سجيف بن قيس في مدينة مصراته، وزهير البلوي وأبو منصور الفارسي وعبد الله بن بر وكلا الثلاثة في مدينة درنة، وتطور الإسلام بانتشار المذهب المالكي وبروز علماء ساهموا في نشره ليس في ليبيا فقط بل في كل أقطار المغرب العربي مثل الشيخ علي بن زياد الطرابلسي، حيث كان المذهب المالكي من بين الأسس في تطور الإسلام في ليبيا، وارتبط بالنواحي المختلفة وشكل هوية لليبيين على مر العصور، كما شكلت الطريقة السنوسية دورا كبيرا في تطور الإسلام في ليبيا ولعبت أدورا مهما في نشر الفقه المالكي والطريقة الصوفية النقية البعيدة عن البدع والخرفات وفي نشر الفقه المالكي وكذلك في حركة الجهاد ضد المستعمر الإيطالي. الكلمات المفتاحية: تطور، العالم، المذهب، الإسلام، ليبيا.